Historical blocking: IN 2019-12-20 (India) - Voidly (Voidly Global Censorship Index, 2019)
WARNING severity censorship detected in India. Data sourced from ooni-historical-backfill.
Censorship Incident ID: IN-2019-0003. Severity: warning. Confidence: 74%